Flavin adenine dinucleotide functionalized gold nanoparticles for the electrochemical detection of dopamine - Medrades, Jennifer de Pontes (2022)
Dopamine (DA) is a neurotransmitter with multiple functions in the central nervous system, and whether found in low levels, activation of biological defense system and physiological activity is influenced. DA at abnormal levels in the body may cause neurodegenerative illnesses such as Parkinson's disease or schizophrenia, so monitoring DA level and intervening as soon as possible is highly desirable. In this work, an electrochemical biosensor was produced on a gold substrate using self-assembled monolayer of 11 mercaptoundecanoic acid (11-Mua), followed by Layer by layer (LbL) technique. For this, a layer of cationic polyelectrolyte poly(ethyleneimine) (PEI), and finally a layer of gold nanoparticles stabilized with glutathione and functionalized with flavin adenine dinucleotide (FAD). FAD is a cofactor present in active site of monoamine oxidase enzyme and confers selectivity to the biosensor. Electrochemical biosensor was characterized by UV-Vis and FTIR spectroscopies, atomic force microscopy (AFM), and electrochemical techniques. Electrochemical detection was performed by differential pulse voltammetry (DPV) in PBS buffer showed a linear range of detection from 0.8 to 8.0 µmol L−1, sensitivity was 1.25 µA/µmol L−1 cm−2, limits of detection and quantification calculated were respectively 0.525 µmol L−1 and 1.75 µmol L−1. Biosensor showed recovery values between 85 and 90% in the study with human urine. According to sensor performance, gold nanoparticles and FAD could be used in electrochemical detection due to their high sensitivity and low detection limit.